Peningkatan Pengetahun Hukum Bagi Yayasan Genggam Teman Indonesia dalam Membangun Kerjasama dengan Pemerintah Kota Bekasi Melalui Kegiatan Edukasi Legal Drafting - Athina Kartika Sari; Sophiyanto Wuryan; Sri Pramudya Wardhani; Nazwa Davina Putri Darmawan (Jurnal Impresi Indonesia, 2026)
The Genggam Teman Indonesia Foundation (GTI) is a social institution that oversees the community of women MSME actors located in Bekasi City. The GTI Foundation has played a role in providing entrepreneurship training, business legality, including: Business Identification Number, Household Industry Food, Halal, and business digitalization. The training is often in collaboration with the Bekasi City Government, but nevertheless one of the important aspects that is still optimized is the aspect of knowledge in the legal field, especially in preparing formal legal documents as the basis for partnerships with local governments. The methods used in this study were interviews, questionnaire distribution, and secondary legal material studies. Based on the results of community service activities held between Esa Unggul University and the Indonesian Handheld Foundation, it is hoped that the training on the preparation of legal drafting can be a means of capacity building and can help the GTI Foundation to strengthen internal governance, increase partner trust, and expand access to collaborative programs of the Bekasi City government that demand legal certainty and administration in accordance with standards. In addition, the GTI Foundation is also expected to be able to process the drafting of legal documents such as the draft agreement with the Bekasi city government. Based on the results of filling out questionnaires with GTI Foundation participants, these activities can increase participants' knowledge as expected and can be followed up by checking the documents of the GTI Foundation's agreement with other institutions by the presenter.